Mini-αA Upregulates the miR-155-5p Target Gene CDK2 and Plays an Antiapoptotic Role in Retinal Pigment Epithelial Cells during Oxidative Stress - Qianyin Chen; Huimin Lin; Shengnan Li; Xuan Deng; Jinglin Zhang (Journal of Ophthalmology)
Background. Age-related macular degeneration (AMD) is the leading cause of serious vision loss in the elderly. Regulating microRNA (miRNA) gene expression offers exciting new avenues for treating AMD. This study aimed to investigate whether miRNAs and their target genes play an antiapoptotic role during oxidative stress-induced apoptosis of retinal pigment epithelial (RPE) cells via mini-αA. Methods. ARPE-19 cells were treated with 3.5 mM NaIO3 for 48 h to establish a retinal degeneration model. Cells were treated with mini-αA (10, 15, and 20 μM) for 4 h. miR-155-5p was knocked down and overexpressed. Cell viability and apoptosis were measured using the Cell Counting Kit-8 assay and flow cytometry, respectively. The reactive oxygen species level was detected by flow cytometry. miR-155-5p target genes were predicted via bioinformatics. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses were performed for miR-155-5p target genes. A quantitative real-time polymerase chain reaction was performed to detect miRNAs and cell cycle-related target genes. Western blotting was performed to measure the levels of apoptotic pathway genes encoding Bcl-2, Bax, cleaved caspase-3, and cyclin-dependent kinase 2 (CDK2). Dual-luciferase reporter gene assay was performed to verify the targeted binding relationship between miR-155-5p and CDK2. Results. NaIO3 can induce oxidative damage and promote apoptosis. Conversely, mini-αA had inhibitory effects and could reverse the oxidative damage and apoptosis triggered by NaIO3 in the retinal degeneration model. The expression of miR-155-5p was upregulated in cells treated with NaIO3 and was downregulated after mini-αA treatment. Furthermore, miR-155-5p can target the following cell cycle-related and proliferation-related genes: CDK2, CDK4, CCND1, and CCND2. Moreover, our study indicated that miR-155-5p was involved in the antioxidative damage and antiapoptotic effects of mini-αA via CDK2 regulation. Conclusions. miR-155-5p promotes the antioxidative damage and antiapoptotic effects of mini-αA during oxidative stress-induced apoptosis of RPE cells via CDK2 regulation. This study provides a new therapeutic target for AMD.